Experimental investigation on the effects of granulated coal ash (GCA) on the water and sediment quality of Estero de San Miguel - Cruz, Gil G. Jr
The use of Granulated Coal Ash (GCA) has been developed in Japan as a potential in situ technology for the improvement of organically enriched sediment. In this study, laboratory experiments were conducted to investigate the effect of GCA on the water and sediment collected from Estero de San Miguel (Manila, Philippines). Batch studies were performed by mixing actual water and sediment from the estero with varying dosages of GCA. The physico-chemical parameters (pH, Oxygen Reduction Potential (ORP), Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Electric Conductivity (EC), Turbidity, Color and Odor) and nutrient concentrations (P04, NH3, N03, N02, S04) in the overlying and pore water were analyzed. The pH, ORP, Ignition Loss (IL), Particle Size Distribution of the sediment were also measured at the start and end of the experiment. The results demonstrated that the improvement in overlying and pore water is mostly evident in decreased concentrations of nutrients. Case 3 (1:1) recorded 46% phosphate removal and 94% ammonia removal concentrations compared to control case in pore water. While in overlying water, Case 3 also recorded 77% phosphate removal and 97% ammonia removal. Moreover, the pH of the sediment with the highest GCA dosage was relatively higher compared to the controlled case which is mainly due to the hydrolysis of calcium oxide (CaO) from the GCA. This increase in pH is deemed to be responsible for the deactivation of sulfate-reducing bacteria in the sediment. Considering the results of batch experiment, GCA has high remediation efficiency in improving water and organically enriched sediment.